(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The wave and tidal energy sectors face significant challenges in developing efficient, safe, and cost-effective mooring systems for anchoring devices in dynamic and harsh marine environments, particularly for prototype devices that may need to be installed and recovered regularly during development. Quick connection mooring systems address these challenges by enabling rapid and secure deployment and retrieval of energy-generating units, significantly reducing installation and maintenance time. By reducing costs and improving logistical efficiency, these advanced mooring systems accelerate the adoption of marine energy technologies. Conceived for renewable energy applications, the C-Dart System offers a groundbreaking approach to safely, efficiently, and quickly connect a variety of vessels, floating infrastructure, and assets such as wave energy converters, tidal energy converters, floating solar, offshore wind, and other floating marine structures. It eliminates the need for personnel transfers or direct handling of heavy mooring lines, drastically reducing the risk of injuries and increasing the weather window for operations. This paper presents the technical background to the design, development, testing and certification of this innovative technology undertaken during the six-year development journey.. The technology development roadmap included extensive analysis, onshore and offshore testing, verification and validation of requirements and ultimately Approval in Principle certification status from Bureau Veritas. This programme of work has led to the demonstration of a prototype 21te load tested mooring system, and Blackfish is now engaging with customers and stakeholders to develop the technology further.